Odpowiedź :
8cm=2a przeciwprostokatna
a przyprostokatna
a√3 druga przyprosokatna
Ob=8cm+4cm+4√3cm=12+4√3cm≈19cm
a przyprostokatna
a√3 druga przyprosokatna
Ob=8cm+4cm+4√3cm=12+4√3cm≈19cm
c=8cm
a-pierwsza przyprostokątna
b-druga przyprostokątna
a²+a²=c²
2a²=64
a²=32
a=√32=4√2
O=2a+c=2*4√2+8=8√2+8
a-pierwsza przyprostokątna
b-druga przyprostokątna
a²+a²=c²
2a²=64
a²=32
a=√32=4√2
O=2a+c=2*4√2+8=8√2+8
a do kwadratu +a do kwadratu=8 do kwadratu
2a do kwadratu=64
a do kwadratu=32
a=pierwiastek z 32=4*pierwiastek z 2
2a do kwadratu=64
a do kwadratu=32
a=pierwiastek z 32=4*pierwiastek z 2